Cuban-US relations: political needs behind the deal - Mazzina, Constanza (2016)
The agreement between Cuba and the United States, the late December 2014, where the resumption of relations between the two countries was agreed, after more than fifty years of interruption shows, a historic change and a reciprocal opportunity. This article analyzes the bilateral relations in political-historical terms and then review the events leading up to the agreement given that this involved a complex negotiation and effort of a number of heterogeneous actors that included from the Canadian government, officials from both sides and even Pope Francisco in the Vatican. Then, the article reflects on the reasons why the deal came and the goals that this has achieved. Finally, it presents outstanding issues to resolve on the bilateral agenda.